(untitled) (Materiali di Estetica. Terza serie, 2014)
The paper analyses a movie recently appeared in Italy, Belluscone (2014) by Franco Maresco. The title refers to the deformation of Berlusconi’s name in Sicily. The movie does not speak, however, of the typically Italian “hero” Berlusconi, but of “Belluscone” that is the link for a common feeling whose Sicily is an exemplary case. Through the reference to Lyotard and Jauss among the others, the aim is to show that “Belluscone” is no longer a symbolic disposition, and becomes a sensible surface of contact to which everybody connects in order to have an experience. With its Baroque and ambiguous investigation of “bellusconian” Palermo, the movie makes no exception.